Concurrent habitat fluctuations of two economically important marine species in the Southeast Pacific Ocean off Chile in relation to ENSO perturbations. (12th November 2021) - Feng, Zhiping; Yu, Wei; Chen, Xinjun
Abstract: ENSO‐driven concurrent habitat fluctuations of two economically important marine species jumbo squid Dosidicus gigas and jack mackerel Trachurus murphyi in the Southeast Pacific Ocean off Chile during 1950–2017 were examined using a habitat suitability index (HSI) modeling approach. The optimal HSI models sourced from 10 weighing‐based scenarios were developed, selected and validated using the crucial factors water temperature at 400 m depth (Temp_400m), sea surface height anomaly (SSHA) and sea surface salinity (SSS) for D. gigas and sea surface temperature (SST), Temp_400m, and mixed layer depth (MLD) for T. murphyi . Results suggested that the optimal HSI model could accurately predict the habitat hotspots for D. gigas and T. murphyi . The ENSO event (indicated by Niño 3.4 index, NI) was significantly related to environmental conditions off Chile. Cross‐correlation revealed positive relationships between NI and SST, SSHA, SSS, and Temp_400m and negative correlation between NI and MLD. Synchronous opposite habitat fluctuations were shown between D. gigas and T. murphyi under different ENSO events. The NI was significantly negatively related to the HSI of D. gigas and positively correlated with the HSI of T. murphyi . Comparing with the El Niño years, suitable habitats of D. gigas and T. murphyi dramatically enlarged and contracted, respectively, during the La Niña years. Both suitable habitats moved southwestward under this climate conditions. Our finding suggested that ENSO‐driven environmental changes played important roles in the concurrent habitat fluctuations of D. gigas and T. murphyi . Such studies are conducive to the effective utilization and management of multiple related species.